Increasing the Quality of Control Operations During Construction and Assembly Works - A., Usmanov I.; A., Muhammadiev U. (Research Parks Publishers, 2023)
The complexity of the construction industry lies not only in the variety of processes, operations and technologies used, but also in the need for constant monitoring of the quality of work. In this regard, along with quality control of work, the quality of control operations is of great importance. This article is devoted to the study of approaches to assessing the quality of control operations. The authors propose to form calculation standards for quality control of construction work, which would ensure the objectivity, accuracy and validity of the time spent on control. These standards form the methodological basis for the development of maps of input, operational and acceptance quality control in the production of construction and installation works.